Notch and presenilin regulate cellular expansion and cytokine secretion but cannot instruct Th1/Th2 fate acquisition. - Chin-Tong Ong; John R Sedy; Kenneth M Murphy; Raphael Kopan (PLoS ONE)
Recent reports suggested that Delta1, 4 and Jagged1, 2 possessed the ability to instruct CD4(+) T cell into selection of Th1 or Th2 fates, respectively, although the underlying mechanism endowing the cleaved Notch receptor with memory of ligand involved in its activation remains elusive. To examine this, we prepared artificial antigen-presenting cells expressing either DLL1 or Jag1. Although both ligands were efficient in inducing Notch2 cleavage and activation in CD4(+) T or reporter cells, the presence of Lunatic Fringe in CD4(+) T cells inhibited Jag1 activation of Notch1 receptor. Neither ligand could induce Th1 or Th2 fate choice independently of cytokines or redirect cytokine-driven Th1 or Th2 development. Instead, we find that Notch ligands only augment cytokine production during T cell differentiation in the presence of polarizing IL-12 and IL-4. Moreover, the differentiation choices of naïve CD4(+) T cells lacking gamma-secretase, RBP-J, or both in response to polarizing cytokines revealed that neither presenilin proteins nor RBP-J were required for cytokine-induced Th1/Th2 fate selection. However, presenilins facilitate cellular proliferation and cytokine secretion in an RBP-J (and thus, Notch) independent manner. The controversies surrounding the role of Notch and presenilins in Th1/Th2 polarization may reflect their role as genetic modifiers of T-helper cells differentiation.